2019
DOI: 10.24198/kultivasi.v18i3.21422
|View full text |Cite
|
Sign up to set email alerts
|

Studi jarak tanam dan naungan terhadap pertumbuhan dan potensi Asystasia gangetica (L.) T. Anderson sebagai tanaman penutup tanah

Abstract: Studi jarak tanam dan naungan terhadap pertumbuhan dan potensi Asystasia gangetica (L.) T. Anderson sebagai tanaman penutup tanahStudy of plant distance and shade on growth and potential of Asystasia gangetica (L.) T. Anderson as cover crop Abstract. Cover crop is one of nature-based agricultural practices that can increase the provision of various ecosystem services in agroecosystems. A. gangetica is a weed that is often found in oil palm plantations and has the potential as a cover crop. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
3
Order By: Relevance
“…This is due to the difference in light intensity received by plants under the shade of teak trees versus those without. Plants in the nonshaded treatment receive more sunlight intensity for photosynthesis than shaded plants (Asbur et al, 2019).…”
Section: Characteristic Morphologymentioning
confidence: 98%
“…This is due to the difference in light intensity received by plants under the shade of teak trees versus those without. Plants in the nonshaded treatment receive more sunlight intensity for photosynthesis than shaded plants (Asbur et al, 2019).…”
Section: Characteristic Morphologymentioning
confidence: 98%
“…Selain itu dengan adanya TPT A. gangetica mampu menambah kandungan hara N, P, K dan C-organik tanah (Tabel 1). Sejalan dengan hasil penelitian ; Asbur et al (2021), bahwa pemanfaatan A. gangetica sebagai TPT mampu menyumbangkan unsur hara N, P, K dan Corganik ke dalam tanah melalui dekomposisi serasahnya. Lebih lanjut Perwitasari et al (2012) menyatakatan bahwa ILD berkaitan erat dengan efisiensi radiasi matahari yang digunakan untuk Keterangan: Angka pada kolom dan baris yang sama diikuti huruf yang berbeda menunjukkan berbeda nyata berdasarkan uji LSD pada taraf 5% Angka pada Rataan (P) dan (T) diikuti huruf yang berbeda menunjukkan berbeda nyata berdasarkan uji LSD pada taraf 5% P1: Pupuk anorganik 0%-organik 100% (10 kg/pohon kompos tankos); P2: Pupuk anorganik 50%-organik 50% (1 kg/pohon urea + 0.75 kg/pohon KCl + 0.75 kg/pohon SP36 + 5 kg/pohon kompos tankos); P3: Pupuk anorganik 100%-organik 0% (2 kg/pohon urea + 1.5 kg/pohon KCl + 1.5 kg/pohon SP36); P4: Pupuk anorganik 100%organik 100% (2 kg/pohon urea + 1.5 kg/pohon KCl + 1.5 kg/pohon SP36 + 10 kg/pohon kompos tankos); T0: Tanpa TPT; T1: TPT A. gangetica Note: Values in the same column and row followed by different letters show significantly different based on the LSD test at 5% level Values on the mean (P) and (T) followed by different letters show significantly different based on the LSD test at the 5% level P1: 0% inorganic-100% organic fertilizer (10 kg/tree tankos compost); P2: 50% inorganic-50% organic fertilizer (1 kg/tree urea + 0.75 kg/tree KCl + 0.75 kg/tree SP36 + 5 kg/tree tankos compost); P3: 100% inorganic-0% organic fertilizer (2 kg/tree urea + 1.5 kg/tree KCl + 1.5 kg/tree SP36); P4: 100% inorganic-100% organic fertilizer (2 kg/tree urea + 1.5 kg/tree KCl + 1.5 kg/tree SP36 + 10 kg/tree tankos compost); T0: Without TPT; T1: TPT A. gangetica Tabel 3.…”
Section: Rataan (P)unclassified
“…Not only Eleocharis dulcis, Asystasia gangetica can also be used as cover and increase the availability of nutrients N, P, K as much as 18.49%,9.20%, 38.36%. A. Gangetica can increase soil carbon stock by 100% compared to soil without groundcover [29,30]. Other studies have shown that besides A. Gangetica, N. Biserrata also has functioned as a cover crop and reduces the water deficit by 51.53%, and contributes nutrients by 15.7 tons dry weight/ha/year or 7.7 tons C/ha/year [31].…”
Section: The Role Of Plant In Maintaining Ecological Balancementioning
confidence: 99%